Silica coated iron oxide nanoparticles-induced cytotoxicity, genotoxicity and its underlying mechanism in human HK-2 renal proximal tubule epithelial cells - Královec, Karel; Havelek, Radim; Kročová, Eliška; Kučírková, Lucie; Hauschke, Martina; Bartáček, Jan; Palarčík, Jiří; Sedlák, Miloš (Mutation research, 2019)
Iron oxide nanoparticles (IONPs) have a great potential with regard to cell labelling, cell tracking, cell separation, magnetic resonance imaging, magnetic hyperthermia, targeted drug and gene delivery. However, a growing body of research has raised concerns about the possible unwanted adverse cytotoxic effects of IONPs. In the present study, the in vitro cellular uptake, antiproliferative activity, cytotoxicity, genotoxicity, prooxidant, microtubule-disrupting and apoptosis-inducing effect of Fe3O4@SiO2 and passivated Fe3O4@SiO2-NH2 nanoparticles on human renal proximal tubule epithelial cells (HK-2) have been studied. Both investigated silica coated IONPs were found to have cell growth-inhibitory activity in a time- and dose-dependent manner. Determination of cell cycle phase distribution by flow cytometry demonstrated a G1 and G2/M phase accumulation of HK-2 cells. A tetrazolium salt cytotoxicity assay at 24 h following treatment demonstrated that cell viability was reduced in a dose-dependent manner. Microscopy observations showed that both Fe3O4@SiO2 and Fe3O4@SiO2-NH2 nanoparticles accumulated in cells and appeared to have microtubule-disrupting activity. Our study also revealed that short term 1 h exposure to 25 and 100 μg/mL of silica coated IONPs causes genotoxicity. Compared with vehicle control cells, a significantly higher amount of γH2AX foci correlating with an increase in DNA double-strand breaks was observed in Fe3O4@SiO2 and Fe3O4@SiO2-NH2-treated and immunestained HK-2 cells. The investigated nanoparticles did not trigger significant ROS generation and apoptosis-mediated cell death. In conclusion, these findings provide new insights into the cytotoxicity of silica coated IONPs that may support their further safer use.
Keywords: histony; povrchové vlastnosti; poškození DNA; virová transformace buněk; Cell Line; Kidney Tubules, Proximal; Silicon Dioxide; Mutagenicity Tests; epitelové buňky; DNA Damage; reaktivní formy kyslíku; Epithelial Cells; proximální tubuly ledvin; Genes, p53; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Magnetite Nanoparticles; Cell Transformation, Viral; Microtubules; Reactive Oxygen Species; magnetické nanočástice; geny p53; lidé; Humans; mikrotubuly; Surface Properties; Cell Cycle; buněčné linie; apoptóza; oxid křemičitý; Ferrosoferric Oxide; Histones; buněčný cyklus; oxid železnato-železitý; Apoptosis; testy genotoxicity